Penggunaan Media Pembelajaran Berbasis Video pada Mata Pelajaran PAI di Sekolah Dasar - Safaruddin, Safaruddin; Amran, Amran; Triandana, Jenita; Arif, Muhammad; Rahman, Yusuf (Yayasan Indonesia Emerging Literacy Education, 2024)
Learning media has a very important role as part of learning. Without using media, the learning process cannot take place optimally. The use of video-based learning media as a student learning resource in PAI learning that takes place in the classroom can stimulate students' creativity and enthusiasm to participate in learning. This research uses qualitative descriptive methods and data collection through literature reviews. The results of this research are the impact of using video media on teachers, including encouraging teachers to use media more creatively, it is easier for teachers to explain subjects, teachers can save more energy when explaining material, and teachers can learn more about the material in the video. the. In addition, the use of video-based learning environments can also encourage active and collaborative learning. Students can directly interact with the video, for example by answering questions, discussing or watching simulation videos.